2016
DOI: 10.1007/s12011-016-0703-6
|View full text |Cite
|
Sign up to set email alerts
|

The Nickel Concentration in Breast Milk during the First Month of Lactation in Yazd, Center of Iran

Abstract: Breastfeeding plays an important role in the growth and development of breastfed infants, especially in the first 6 months of their lives. The present study was conducted to determine the nickel concentrations in breast milk of lactating women in Yazd, Iran. One hundred fifty volunteers were selected among nursing mothers referring to health centers in Yazd. In the first month of lactation, milk samples were collected three times, on days 3 to 5 (first), 16 (Second), and 30 (third) after delivery. Nickel conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Further, a low level of Ni was found in our HM samples, being the Ni concentration lower than that reported in previous studies conducted in Spain ( Martínez et al, 2019 ) and Iran ( Salmani et al, 2016 ) ( Table A2 ). However, investigations conducted in Sweden ( Björklund et al, 2012 ) and Brazil ( Cardoso et al, 2014 ) found Ni levels in HM even lower than observed in the present study ( Table A2 ).…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…Further, a low level of Ni was found in our HM samples, being the Ni concentration lower than that reported in previous studies conducted in Spain ( Martínez et al, 2019 ) and Iran ( Salmani et al, 2016 ) ( Table A2 ). However, investigations conducted in Sweden ( Björklund et al, 2012 ) and Brazil ( Cardoso et al, 2014 ) found Ni levels in HM even lower than observed in the present study ( Table A2 ).…”
Section: Resultscontrasting
confidence: 83%
“…The Agency for Toxic Substance and Disease Registry indicates that the Ni concentration in breast milk is either similar to or less than that in cow's milk-based or soy-based infant formula ( ATSDR, 2005 ). Contaminated water and food, as well as inhalation of tobacco smoke may increase the Ni concentration in breast milk ( Salmani et al, 2016 ). The low Pb, Cd, and Ni concentrations found in this study are possibly due to the non-smoking habits reported by our breast milk donors.…”
Section: Resultsmentioning
confidence: 99%
“…In a study from Yazd, Iran, the mean Ni levels in breast milk samples on days 3–5, 16, and 30 after delivery were 47.3 ± 7.40, 49.9 ± 8.05, and 54.8 ± 7.38 μg/l, respectively. Also, its concentration in more than 86% of samples was higher than the permissible limits 60 . Osmar (2014) also found that breast milk from 48 Brazilian women living in Minas Gerais contained lower levels of nickel than WHO reference levels 61 .…”
Section: Discussionmentioning
confidence: 78%
“…Sources of nickel include emissions from motor vehicles and electric power utilities, as well as food and drinking water. Available data indicate that nickel content in human milk is around 55 μg L −1 and, overall, chronic dietary exposure to nickel in infants ranges from around 28 to 30 μg kg −1 of body weight per day [ 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%